Novel and potent anti-tumor and anti-metastatic di-2-pyridylketone thiosemicarbazones demonstrate marked differences in pharmacology between the first and second generation lead agents - Sestak, Vit; Stariat, Jan; Cermanova, Jolana; Potuckova, Eliska; Chladek, Jaroslav; Roh, Jaroslav; Bures, Jan; Jansova, Hana; Prusa, Petr; Sterba, Martin; Micuda, Stanislav; Simunek, Tomas; et al. (Oncotarget, 2015)
Di(2-pyridyl)ketone 4,4-dimethyl-3-thiosemicarbazone (Dp44mT) and di(2-pyridyl)ketone 4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC) are novel, highly potent and selective anti-tumor and anti-metastatic drugs. Despite their structural similarity, these agents differ in their efficacy and toxicity in-vivo. Considering this, a comparison of their pharmacokinetic and pharmaco/toxico-dynamic properties was conducted to reveal if these factors are involved in their differential activity. Both compounds were administered to Wistar rats intravenously (2 mg/kg) and their metabolism and disposition were studied using UHPLC-MS/MS. The cytotoxicity of both thiosemicarbazones and their metabolites was also examined using MCF-7, HL-60 and HCT116 tumor cells and 3T3 fibroblasts and H9c2 cardiac myoblasts. Their intracellular iron-binding ability was characterized by the Calcein-AM assay and their iron mobilization efficacy was evaluated. In contrast to DpC, Dp44mT undergoes rapid demethylation in-vivo, which may be related to its markedly faster elimination (T1/2 = 1.7 h for Dp44mT vs. 10.7 h for DpC) and lower exposure. Incubation of these compounds with cancer cells or cardiac myoblasts did not result in any significant metabolism in-vitro. The metabolism of Dp44mT in-vivo resulted in decreased anti-cancer activity and toxicity. In conclusion, marked differences in the pharmacology of Dp44mT and DpC were observed and highlight the favorable pharmacokinetics of DpC for cancer treatment.
Keywords: Male; Rats, Wistar; protinádorové látky; preklinické hodnocení léčiv; anti-cancer agents; Cell Line, Tumor; di(2-pyridyl)ketone 4-cyclohexyl-4-methyl-3-thiosemicarbazone; Thiosemicarbazones; vysokoúčinná kapalinová chromatografie; tandemová hmotnostní spektrometrie; Di(2-pyridyl)ketone 4,4-dimethyl-3-thiosemicarbazone; mužské pohlaví; potkani Wistar; Chromatography, High Pressure Liquid; krysa rodu Rattus; Animals; lidé; Humans; pharmacokinetics; Drug Evaluation, Preclinical; zvířata; Rats; Tandem Mass Spectrometry; nádorové buněčné linie; thiosemikarbazony; Antineoplastic Agents; metabolism